Indonesian Christian International Students in Australia: (Re)Constructing Religious Identities - Mulya, Teguh Wijaya (ANIMA Indonesian Psychological Journal, 2011)
Indonesian Christians international students are experiencing new religio-cultural experiencesduring their study in Australia. Some of those experiences are contradictory with theirChristian beliefs. This study seeks to understand the way Indonesian Christian internationalstudents in Australia negotiating their cultural and religious identity. In this qualitativestudy, I interviewed four Indonesian Christian international students in Australia includingmyself. The findings describe participants’ tensions between their Christian beliefs and newreligio-cultural experiences during participants’ study in Australia, such as questions aboutsexuality, feminism, and various knowledges met in their university studies. Participantsconstructed their new ways of being a Christian by demonstrating different markers ofevangelical Christianity, liberal Christianity, and spiritual seekers (Mathews, 2000). Mahasiswa Kristen Indonesia di Australia menjumpai berbagai pengalaman budaya danreligius yang baru selama menempuh studinya. Beberapa pengalaman baru tersebut mengundangpertanyaan tentang iman Kristen mereka selama ini. Penelitian ini bertujuan memahamipengalaman mahasiswa-mahasiswa Kristen tersebut menegosiasikan identitas agama danbudaya mereka. Dalam penelitian kualitatif ini empat mahasiswa Indonesia diwawancarai,termasuk peneliti sendiri. Hasil penelitian menunjukkan adanya ketegangan antara imanKristen mereka dan pengalaman budaya dan religius baru selama studi mereka di Australia,seperti pertanyaan seputar seksualitas, kesetaraan gender, dan pengetahuan-pengetahuanbaru di bidang studi mereka masing-masing. Partisipan menegosiasikan dan membangunkembali identitas Kristen mereka; misalnya dengan menjadi Kristen injili, liberal, atau pelancongspiritual (Mathews, 2000)